Association of Allele 61888G>T Polymorphism VDR Gene and Colorectal Cancer - M Haghighi,; SR Mohebbi; MA Pour Hoseingholi,; MY Taleghani,; SR Fatemi; MR Zali (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2010)
BACKGROUND AND OBJECTIVE: Colorectal cancer is the third most common cancer in the world and it is the fourth most common cancer that is a leading cause of cancer deaths. Polymorphisms of the vitamin D receptor (VDR) gene may influence colorectal cancer risk. The vitamin D receptor (VDR) is a crucial mediator for the cellular effects of vitamin D and additionally interacts with other cell-signaling pathways that influence cancer development. The purpose of this study was to investigate single nucleotide polymorphism of the vitamin D receptor gene and its possible relationship with colorectal cancer (CRC) in an Iranian population. METHODS: This investigation was a case control study. The samples were including 130 CRC patients and 130 controls referred to Taleghani hospital, Tehran. These individuals considering their pathological results are divided into two groups. Due to genotyping of vitamin D receptor (VDR) genotypes polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) was performed and restriction enzyme, Apa1, was used. FINDINGS: The frequencies of the GG, TG, and TT genotypes were 10%, 43.8% and 46% in healthy controls and 21.5%, 44.6% and 33.8% in colorectal cancer patients, respectively. Furthermore, frequency of T allele was 68%, 44%, and the C allele was 32% and 56% in the control group and colorectal cancer patients respectively.CONCLUSION: According to our finding, interestingly we could detect a reverse association between genotype 61888G>T and colorectal cancer.